Metabolic Capabilities of Microorganisms Involved in and Associated with the Anaerobic Oxidation of Methane - Wegener, Gunter; Krukenberg, Viola; Ruff, S. Emil; Kellermann, Matthias Y.; Knittel, Katrin (Frontiers in Microbiology, 2016)
In marine sediments the anaerobic oxidation of methane with sulfate as electron acceptor (AOM) is responsible for the removal of a major part of the greenhouse gas methane. AOM is performed by consortia of anaerobic methane-oxidizing archaea (ANME) and their specific partner bacteria. The physiology of these organisms is poorly understood, which is due to their slow growth with doubling times in the order of months and the phylogenetic diversity in natural and in vitro AOM enrichments. Here we study sediment-free long-term AOM enrichments that were cultivated from seep sediments sampled off the Italian Island Elba (20°C; hereon called E20) and from hot vents of the Guaymas Basin, Gulf of California, cultivated at 37°C (G37) or at 50°C (G50). These enrichments were dominated by consortia of ANME-2 archaea and Seep-SRB2 partner bacteria (E20) or by ANME-1, forming consortia with Seep-SRB2 bacteria (G37) or with bacteria of the HotSeep-1 cluster (G50). We investigate lipid membrane compositions as possible factors for the different temperature affinities of the different ANME clades and show autotrophy as characteristic feature for both ANME clades and their partner bacteria. Although in the absence of additional substrates methane formation was not observed, methanogenesis from methylated substrates (methanol and methylamine) could be quickly stimulated in the E20 and the G37 enrichment. Responsible for methanogenesis are archaea from the genus Methanohalophilus and Methanococcoides, which are minor community members during AOM (1 to 7‰ of archaeal 16S rRNA gene amplicons). In the same two cultures also sulfur disproportionation could be quickly stimulated by addition of zero-valent colloidal sulfur. The isolated partner bacteria are likewise minor community members (1 to 9‰ of bacterial 16S rRNA gene amplicons, whereas the dominant partner bacteria (Seep-SRB1a, Seep-SRB2 or HotSeep-1) did not grow on elemental sulfur. Our results support a functioning of AOM as syntrophic interaction of obligate methanotrophic archaea that transfer non-molecular reducing equivalents (i.e. via direct interspecies electron transfer) to obligate sulfate-reducing partner bacteria. Additional katabolic processes in these enrichments but also in sulfate methane interfaces are likely performed by minor community members.